The Impact of Drowsiness on Road Traffic Accidents in Yogyakarta - Widyastuti, Nur Rachmi; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Traffic accidents are a serious issue in Yogyakarta, with one of the leading causes being drowsy driving. Drowsiness while driving can reduce alertness, response time, and the driver's ability to react to emergency situations, thereby increasing the risk of accidents. This phenomenon not only causes material losses but also endangers the lives of drivers, passengers, and other road users.This study aims to analyze the impact of drowsiness on traffic accidents in Yogyakarta, identify factors influencing drowsiness while driving, and provide recommendations to reduce the risk of accidents caused by driver fatigue and sleepiness on the road. This study uses a quantitative approach, gathering data from traffic accident records in Yogyakarta over the past year. Additionally, a survey was conducted with drivers involved in accidents to measure their level of drowsiness while driving, duration of travel, and other related factors. The data were analyzed using Descriptive methods to examine the relationship between drowsiness and accident incidents.The study found a significant correlation between drowsiness while driving and the increased risk of accidents in Yogyakarta, especially during late night and early morning hours. Drivers who traveled long distances without adequate rest were at higher risk. Accidents most frequently occurred among drivers traveling for more than 2 hours without a break, particularly between 11:00 p.m. and 5:00 a.m. Further public education is needed regarding the dangers of drowsy driving. Additionally, it is recommended to increase the availability of rest areas and checkpoints on main roads, especially during high-risk times. The implementation of drowsiness detection technology in vehicles may also provide a solution to reduce drowsiness-related accidents.